SENSORY PROPERTIES OF CUSTARD SOY-BASED DESSERTS PREDICTED BY RAPID INSTRUMENTAL MEASUREMENTS - SPADA, JORDANA C.; MARCZAK, LIGIA DAMASCENO FERREIRA; TESSARO, ISABEL CRISTINA; FLÔRES, SIMONE HICKMANN; CARDOZO, NILO SÉRGIO MEDEIROS (Boletim do Centro de Pesquisa de Processamento de Alimentos, 2017)
The aim of this work was to assess to what extent rheological properties can explain the sensory texture in soy based desserts containing different amounts of water soluble soy extract, modified starch and guava pulp, as well as to correlate the sensory and instrumental color. Seventeen creamy soy based desserts were studied. Sensory ranking tests were performed by Quantitative Descriptive Analysis (QDA) and affective sensory tests. Correlations between sensory and instrumental data were determined using Pearson’s correlation coefficient. Results showed a moderate positive correlation between sensory color and a*, and significant negative correlations with L* and hab. Loss modulus at 1 and 10 rad s-1 and the parameters n” were the rheological parameters better correlated with the sensory attributes related to consistency and creaminess. Moreover, the results found in the affective tests can be explained by those verified in QDA